Epidemiological patterns of Tuberculosis disease in the Babol, Iran - Saber Ghaffari-Fam; Seyed Reza Hosseini; Hassan Heydari; Roghaye Vaseghi-Amiri; Amin Daemi; Hossein Ali Nikbakht (Journal of Analytical Research in Clinical Medicine, 2015)
Introduction: Almost one-third of the world’s population is at risk of exposure to tuberculosis (TB) infection. The aim of this study is to describe some patterns of TB in the Babol, Iran, to analyze the current situation and to improve the care of these patients. Methods: This was a cross-sectional study. The data were obtained from medical records pertained to patients with TB of Health Network of Babol County. The variables of interest were demographic characteristics and some clinical patterns. To describe data, indices such as mean ± SD and frequency (percent) was used. Furthermore, analysis of the data was performed by inferential statistical techniques of chi-square, independent samples t-test, and one-way analysis of variance test. Results: Two hundred patients with TB were enrolled. The average age of cases were 47.51 years [standard deviation (SD) = 21.36] and 58.5% of them were males. Age groups of 18-40 and over 60 years old comprised the majority of patients with TB 39.0 and 31.5%, respectively. The median interval time between beginning symptoms and confirmed diagnosis of TB was 56.5 days with interquartile range (IQR) of 56 days. The greatest of the time interval of beginning symptoms and diagnosis belonged to the age group of below 7 years old. The greatest time interval from confirmed diagnosis to treatment pertained to the age groups of 18-40 and 7-18, respectively. In terms of pulmonary TB, 120 (80.0%) were smear positive and 30 (20.0) smear negative. In terms of medicines given to the patients with TB, 181 (90.5%) were completed the treatment and improved, 6 (3.0%) absence of treatment, and 13 (6.5%) died as a result of TB and other causes.Conclusion: This study showed that adults and elderly comprise the highest proportion of TB. The primary prevention and control programs for education and timely referral to the Health Network may be effective in diminishing the morbidity due to TB.